EVALUASI MANAJEMEN BERBASIS SEKOLAH (MBS)DI SMP NEGERI BOJA KABUPATEN KENDAL - Widjajanti, Rita; Sulasmono, Bambang Suteng (Kelola: Jurnal Manajemen Pendidikan, 2015)
The study aimed to evaluate 1) whether the PAKEM plan carried out as a fulfillment ofÂ the standardized goal-oriented learning plan. 2) The performance of PAKEM learningÂ carried out looking into whether it is in accordance with the goal-oriented plans. 3)The outputs of PAKEM learning, measured by the achievement of the learning objectives.Â The research conducted here has applied an evaluative approach using both quantitativeÂ and qualitative methodology. This research was conducted in SMPN 2 Boja KendalÂ regency. The respondents assigned to the research were principal, 20 classroom teachersÂ of IX grade and 30 students of class IX C. The data collection techniques usedÂ observation, documentation study and interview. The quantitative data analysis wasÂ conducted to gain the results of the data of observation and of studying the documents,Â whereas the qualitative data analysis was carried out to examine the results of theÂ interviews. The research showed that (1) the PAKEM learning plan carried out hadÂ fulfilled the standardized goal-oriented learning plan. Nevertheless, the teachersâÂ competence in selecting and making use of teaching media needs improving. TeachersÂ as individuals or with the support of school may do this either. (2) The performance ofÂ PAKEM learning carried out has been done well in accordance with the goal-orientedÂ plan because all the teachers have achieved good grades of teaching performance.Â However, to enhance their teaching performance, it is necessary for the teachers toÂ improve their competence in making use of the available learning and teaching sources, teaching media and in assessing the students learning. (3) The outputs of PAKEMÂ learning have been able to measure the goal achievement of learning. This has beenÂ proven by the fact that a lot of students have passed most of the school subjects (8Â subjects) achieving grades higher than the minimum grades required to pass them.Â Referring to the minimum grade required to pass the subjects, only a few students haveÂ not passed 4 of them. Nevertheless, school needs to gradually raise the minimum passingÂ grade in order to be equal to the national one.